Parenting and family self-sufficiency services contribute to impacts of Early Head Start for children and families - Chazan-Cohen, Rachel; Von Ende, Adam; Lombardi, Caitlin (Frontiers in Psychology, 2023)
There is evidence that two-generation early childhood programs, those that strive to support not only child development, but also optimal parenting and family well-being, help to foster resilience for young children and their families in the face of adversity. Using data from a large experimental evaluation, the Early Head Start Research and Evaluation Project, this paper explores how parenting and family self-sufficiency services embedded in Early Head Start (EHS), a federally funded, nationally implemented two-generation early childhood program for low-income families lasting from pregnancy and until children are three, contribute to the impacts of the program for both the children and their families. Parenting support in any modality (home visiting, case management or parent education) contributed to program impacts on important child and family outcomes, but not parent employment. Somewhat surprisingly, family receipt of employment services did not lead to any of the impacts of the program, while education and job training services did. When EHS parents